The Institutional Dimension of Integration in Marine Spatial Planning: The Case of the Dutch North Sea Dialogues and Agreement - Spijkerboer, Rozanne C. (Frontiers in Marine Science, 2021)
In Marine spatial planning (MSP) literature identifies various dimensions of integration to deal with fragmented, sectoral, and ad hoc approaches to managing various uses offshore. However, the spatial dimension of MSP has receded into the background, the dimensions of integration remain ill-defined, and there is a lack of appreciation for the institutional changes that these integration efforts induce and require. Moreover, in light of the urgency of energy transition, offshore wind farms (OWF) are often prioritized over other interests in MSP practice. This paper uses the case of the Dutch North Sea Dialogues (NSD) to explore to what extent actors during the NSD pursued formal and informal institutional change to progress the various dimensions of integration in line with the normative principles of MSP to improve spatial integration between OWF and other interests at sea. The NSD provided an, initially temporary, platform that proved key for stakeholders to pursue subsequent formal and informal institutional changes that progressed integration in MSP. While formal institutional changes were achieved during the NSD, informal institutional changes also proved fundamental in progressing various dimensions of integration. The NSD shows that incremental institutional change can be effective in progressing integration, but also shows the limits to this approach. The place-based and temporal dimension of integration requires additional attention because this is where stakeholders most notably rely on existing institutional frameworks and conflicts are most prominent.